2019
DOI: 10.1149/2.10219113jes
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Developed Electrochemical Method for the Simultaneous Determination of Camylofin and Analgine in Pharmaceutical Preparation and Biological Fluids

Abstract: A simple, rapid and highly sensitive electrochemical sensing platform has been developed for the simultaneous determination of Camylofin (CAM) and Analgine (ANG). The electrochemical oxidation based on bare and bulk zinc oxide nanoparticles (ZnO/NPs) and ionic liquid (IL) modified carbon paste electrode (ZnO/IL/MCPE) have been studied using cyclic voltammetry and square-wave voltammetric techniques. Under optimum conditions, the linearity range was from 1 μmol L −1 to 100 μmol L −1 and 0.2 μmol L −1 to 100 μmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The electrooxidation related to proton exchange in buffer solution. [26][27][28] Optimization of experimental conditions.-Effect of pH.-The effect of pH is well known to have a prime impact on the response of organic and inorganic drug compounds. 29 This parameter was studied to detect the oxidation process of IMD at (bare CPE, GNP/MWCNT) in pH range 2 to 10 using B-R buffer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrooxidation related to proton exchange in buffer solution. [26][27][28] Optimization of experimental conditions.-Effect of pH.-The effect of pH is well known to have a prime impact on the response of organic and inorganic drug compounds. 29 This parameter was studied to detect the oxidation process of IMD at (bare CPE, GNP/MWCNT) in pH range 2 to 10 using B-R buffer.…”
Section: Resultsmentioning
confidence: 99%
“…4a) is the response of peak current as a function of pH where it is observed that pH 4 BR buffer provides the highest anodic current. 26 Effect of scan rate.-The interfacial reaction of IMD at each electrode was identified by recording the cyclic voltammograms of 1 × 10 -5 mol l −1 solution at different scan rates (υ)20-150 mV s −1 in B-R buffer (pH 4.0) for bare CPE, GNP/MWCNT.…”
Section: Resultsmentioning
confidence: 99%
“…69,70 Ionic liquid modified carbon paste electrodes with ZnO nanoparticles have been used to simultaneously detect the drugs Analgine and Camylofin. 71 Multiwalled carbon nanotube (MWCNT) structures with Zinc nanoparticles have been used for the simultaneous detection of two antidepressant 41 The aggregation of target antigens is monitored by the development of color and magnetic field. drugs.…”
Section: Urea Diet Starvationmentioning
confidence: 99%
“…It has been used in a variety of applications, including sensing and catalysis [38]. The modified carbon paste electrode (MCPE) was found to be superior to the unmodified one because the unmodified electrode has some drawbacks such as slow electron transfer, low sensitivity, and reproducibility [39]. Nanomaterials, transition metal compounds, and multi-walled carbon nanotubes (MWCNT) are used to resolve these drawbacks.…”
Section: Introductionmentioning
confidence: 99%